Thermally altered coal from Upper Silesian Coal Basin - Klika,Z.; Osovsky,M. (Journal of the Czech Geological Society, 1999)
Chemical composition of organic matter of coal, minerals and chemical composition of inorganic elements of coal were studied from 33 coal samples of coal seam 512(39), where thermally altered coal are present. Volatile matter and combustion heat were determined from other 300 samples from coal seams 530(38), 512(39), and 504(40). Using this data the process of coal alteration was interpreted. The coal seams 530(38) and 504(40) were altered at low temperature conditions while coal seam 512(39) was altered at high temperature condition. Also coal altered both thermally and by oxidation was found in this coal seam. It is supposed that source of heat was coal oxidation (undersurface combustion) of a part of coal seams 512(39) deposited in space of present red beds body which burned out
Keywords: coal; red beds; oxidation; thermal alteration